Analysis of contact graph routing enhancements for DTN space communications. (3rd September 2015) - Bezirgiannidis, N.; Caini, C.; Tsaoussidis, V.
Summary: In this paper, we analyze the performance of two contact graph routing (CGR) enhancements, namely, CGR with earliest transmission opportunity (CGR‐ETO) and overbooking management. CGR‐ETO aims to improve the accuracy of predicted bundle delivery time by exploiting existing information on queueing delay, in routing decisions. Overbooking management aims to proactively handle contact oversubscription, which occurs when high‐priority bundles are forwarded to a contact that is already fully subscribed by lower‐priority bundles. These two enhancements have been recently included in the official CGR version as part of the Interplanetary Overlay Network delay‐tolerant/disruption‐tolerant networking implementation maintained by the National Aeronautics and Space Administration. In parallel to the comparative evaluation of the enhancements against the original CGR, we introduce an experimental version of CGR‐ETO that exploits information on locally routed data to calculate queueing delays in all hops through the path to destination, rather than in the first hop only. We evaluate the aforementioned enhancements in a set of emulation experiments conducted on a GNU/Linux testbed and compare official and experimental versions of CGR. Results show that the two enhancements are complementary and can significantly improve routing decisions compared with older versions of CGR, particularly in the presence of parallel routes and traffic of different priorities. These advantages are further extended when the experimental version of ETO is considered. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this paper, the performance of two contact graph routing (CGR) enhancements, namely, CGR with earliest transmission opportunity and overbooking management are analyzed. These two enhancements have been recently included in the official CGR version as part of the Interplanetary Overlay Network delay‐tolerant/disruption‐tolerant networking implementation maintained by the National Aeronautics and Space Administration Jet Propulsion Laboratory. Results show that the two enhancements are complementary and can significantly improve routing decisions compared with older versions of CGR.